Effect of FcRn antagonism on protective antibodies and to vaccines in IgG-mediated autoimmune diseases pemphigus and generalised myasthenia gravis. (17th November 2022) - Guptill, Jeffrey T.; Sleasman, John W.; Steeland, Sophie; Sips, Magdalena; Gelinas, Deborah; de Haard, Hans; Azar, Antoine; Winthrop, Kevin L.
Abstract: Antagonism of the neonatal Fc receptor (FcRn) by efgartigimod has been studied in several autoimmune diseases mediated by immunoglobulin G (IgG) as a therapeutic approach to remove pathogenic IgGs. Whereas reduction of pathogenic titres has demonstrated efficacy in multiple autoimmune diseases, reducing total IgG could potentially increase infection risk in patients receiving FcRn antagonists. The objective of this study was to analyse the effect of FcRn antagonism with efgartigimod on existing protective antibody titres and the ability to mount an immune response after vaccine challenge. Serum levels of total IgG and protective antibodies against tetanus toxoid (TT), varicella zoster virus (VZV), and pneumococcal capsular polysaccharide (PCP) were measured in all patients enrolled in an open-label trial of efgartigimod for the treatment of pemphigus. Vaccine specific-responses were assessed by measuring changes in IgG titres in patients with generalised myasthenia gravis (gMG) who were treated with efgartigimod and who received influenza, pneumococcal, or coronavirus disease 2019 (COVID-19) vaccines during participation in the double-blind trial ADAPT or open-label extension, ADAPT+ ( n = 17). FcRn antagonism reduced levels of protective anti-TT, anti-VZV, and anti-PCP antibodies and total IgG to a similar extent; anti-TT and anti-VZV titres remained above minimally protective thresholds for the majority of patients, (10/12) 83% and (14/15) 93% respectively. Protective antibodies returned to baseline values upon treatment cessation. Antigen-specific IgG responses to influenza, pneumococcal, and COVID-19 immunisation were detected in patients with gMG who received these vaccines while undergoing therapy with efgartigimod. In conclusion, FcRn antagonism with efgartigimod did not hamper generation of IgG responses but did transiently reduce IgG titres of all specificities. Graphical Abstract: UF0001